New onset of isolated adrenocorticotropin deficiency associated with encephalopathy following coronavirus disease 2019 in a healthy elderly man - Yusuke Yamasaki; Ichiro Horie; Riyoko Shigeno; Shinpei Nishikido; Toshiyuki Ikeoka; Takuro Hirayama; Yohei Tateishi; Akira Tsujino; Atsushi Kawakami (Endocrine Journal)
Coronavirus disease 2019 (COVID-19) due to a severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection can include various systemic organ disorders including endocrinopathies and neurological manifestations. We report the case of a 65-year-old Japanese man who developed isolated adrenocorticotropic hormone (ACTH) deficiency and encephalopathy following SARS-CoV-2 infection. Two weeks after his COVID-19 diagnosis, he was emergently admitted to our hospital because of subacute-onset delirium. On admission, he presented hyponatremia (128 mEq/L) and secondary adrenal insufficiency (ACTH <1.5 pg/mL, cortisol 0.53 μg/dL). Brain imaging and laboratory examinations including SARS-CoV-2 polymerase chain reaction testing in the cerebrospinal fluid revealed no abnormalities. His consciousness level worsened despite the amelioration of hyponatremia by intravenous hydrocortisone (100 mg/day), but his neurological presentations completely resolved after three consecutive days of high-dose (400 mg/day) hydrocortisone. His encephalopathy did not deteriorate during hydrocortisone tapering. He continued 15 mg/day hydrocortisone after discharge. His encephalopathy might have developed via a disturbance of the autoimmune system, or a metabolic effect associated with adrenal insufficiency, although the time lag between the hyponatremia’s improvement and the patient’s neurological response to the steroid was incompatible with common cases of delirium concurrent with adrenal insufficiency. At 13 months after his hospitalization, the patient’s neurological symptoms have not recurred and he has no endocrinological dysfunctions other than the remaining ACTH deficiency. A thorough consideration of the immunological and metabolic characteristics of SARS-CoV-2 is advisable when clinicians treat patients during and even after their COVID-19 disease period.